EFEKTIVITAS ANTARA KOMPRES HANGAT DAN PLESTER KOMPRES DEMAM DENGAN PENURUNAN SUHU TUBUH BAYI TERHADAP IMUNISASI CAMPAK DI WILAYAH KERJA PUSKESMAS TELAGA - Andi Akifa Sudirman; Dewi Modjo; Ferawati Aridi (Zaitun (Jurnal Ilmu Kesehatan), 2020)
The study aimed to determine the effectiveness of warm water compresses and fever compress plasters to reduce baby's body temperature after measles immunization. The study was conducted at Telaga Health Center. This type of research is pre-experiment with pretest-posttest design. There were 20 respodents samples of the research who were taken by using accidental sampling technique. The samples were devided into 2 groups, 10 babies in intervention group were given warm water compress and 10 babies were treated with fever compress plaster. The data were analyzed by using paired t test and independent t test with  level of significancy was 5% (α = 0.05). The result showed that warm water compresses (t count = 41,333 and ρ = 0,000) and fever compress plaster (t count = 47,940 and ρ = 0,000). It indicated that warm water and fever plasters are effective in reducing the baby's body temperature after measles immunization at Telaga Health Center. There was no difference in the effectiveness of warm water compresses with fever compress plasters in lowering the baby's body temperature (t count = 0.793 and ρ = 0.438). It is recommended to health care professionals at Telaga Health Center to be able to provide non-pharmacological interventions such as warm water compresses and fever plasters compresses to reduce babies’ body temperature after measles immunization.